2019
DOI: 10.14735/amko2018139
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal Metastasis in a Breast Cancer Treated with Two Lines of Intrathecal Chemotherapy – a Case Report

Abstract: Background: Leptomeningeal metastasis (LM) in breast cancer is associated with a poor prognosis. Although no randomised trial has demonstrated that intrathecal chemotherapy actually prolongs survival, this treatment is considered standard of care in this setting. The prognosis of patients with LM is poor, with a median overall survival time of less than 6 months. Methods: Herein, we report a case of a young woman with breast cancer who presented with LM at the time of relapse and was subsequently treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our case, however, demonstrated that the methotrexate contributed to the pancytopenia, malaise and oral ulcers via systemic absorption and improved with dose reduction. While additional studies have confirmed that intrathecal methotrexate does not prolong survival, rather it alleviates symptoms, it remains among the standard of care options 11 12…”
Section: Discussionmentioning
confidence: 99%
“…Our case, however, demonstrated that the methotrexate contributed to the pancytopenia, malaise and oral ulcers via systemic absorption and improved with dose reduction. While additional studies have confirmed that intrathecal methotrexate does not prolong survival, rather it alleviates symptoms, it remains among the standard of care options 11 12…”
Section: Discussionmentioning
confidence: 99%